Cognitive and motor aspects of a coincidence-timing task in Cerebral Palsy children. (18th August 2015) - Olivier, I.; Baker, C.; Cordier, J.; Thomann, G.; Nougier, V.
Highlights: New knowledge about anticipation-coincidence in CP children. CP children made similar temporal errors than healthy children in the verbal condition. CP children made greater temporal errors when providing a motor response. CP children partially took into account their sensory-motor deficits. Abstract: Cerebral Palsy (CP) is a clinical syndrome involving postural and motor deficits. CP children are less accurate than healthy ones when trying to reach a target. Thus, it is difficult for CP children to perform anticipation-coincidence tasks requiring temporal and/or spatial accuracy to reach the target at the good place in the right time. The purpose of the present experiment was to further investigate CP children's ability to perform anticipation-coincidence tasks, by dissociating the cognitive from the motor aspects of the task. 11 CP children aged 6–14 years, 51 healthy children aged 6–13 years, and 13 healthy adults performed, as accurately as possible, a coincidence-timing in response to a specific sound of a musical sequence. Two experimental conditions were manipulated: In the verbal condition, temporal estimation occurred through a simple verbal response whereas in the motor condition, temporal estimation was performed by reaching a target at a self-paced velocity. In the verbal condition, CP children made similar temporal errors than their healthy counterpart. However, even though all participants underestimated stimulus occurrence, CP children also exhibited greater and more variable temporal errors when they provided a motor response for estimating stimulus occurrence. These data suggested that CP children were able to anticipate stimulus occurrence and to partially take into account their sensory-motor deficits to reach the target at this time occurrence.